2006
DOI: 10.1007/bf03178576
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on in vitro tumor cell killing by focused bi-frequency ultrasound activated hematoporphyrin derivatives

Abstract: The method of killing tumor cells by focused bi-frequency ultrasound activated hematoporphyrin derivatives is presented and evaluated in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The activation of the T-cell system in tumor tissue by up-regulation of prothymosin alpha, cytotoxic T lymphocyte-associated protein 2 alpha, and the T-cell specific GTPase [27] could be observed. The up-regulation of annexin A1-lipocortin 1 in the tumors treated with short-pulse focused ultrasound beams and the up-regulation of the CD14 antigen and other genes support the hypothesis that application of short-pulse focused ultrasound beams does induce apoptosis [28,29]. The other up-regulated genes induce a variety of cellular processes, such as genes regulating the replication of DNA, transcription, and protein biosynthesis or regulation of the cell cycle and cell proliferation.…”
Section: Discussionsupporting
confidence: 54%
“…The activation of the T-cell system in tumor tissue by up-regulation of prothymosin alpha, cytotoxic T lymphocyte-associated protein 2 alpha, and the T-cell specific GTPase [27] could be observed. The up-regulation of annexin A1-lipocortin 1 in the tumors treated with short-pulse focused ultrasound beams and the up-regulation of the CD14 antigen and other genes support the hypothesis that application of short-pulse focused ultrasound beams does induce apoptosis [28,29]. The other up-regulated genes induce a variety of cellular processes, such as genes regulating the replication of DNA, transcription, and protein biosynthesis or regulation of the cell cycle and cell proliferation.…”
Section: Discussionsupporting
confidence: 54%
“…Hematoporphyrin is an endogenous porphyrin produced by hydrolysis of hemoglobin. It has been reported that hematoporphyrin could inhibit the proliferation of tumor cells 3537. The level of hematoporphyrin in EPS1-1 group was higher than the Model group, showing that EPS1-1 could induce the production of hematoporphyrin to suppress the growth of colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 86%